2001
DOI: 10.1093/jexbot/52.358.919
|View full text |Cite
|
Sign up to set email alerts
|

Viability loss of neem (Azadirachta indica) seeds associated with membrane phase behaviour

Abstract: Storage of neem (Azadirachta indica) seeds is difficult because of their sensitivity to chilling stress at moisture contents (MC) > or =10% or imbibitional stress below 10% MC. The hypothesis was tested that an elevated gel-to-liquid crystalline phase transition temperature (Tm) of membranes is responsible for this storage behaviour. To this end a spin probe technique, Fourier transform infrared microspectroscopy, and electron microscopy were used. The in situ Tm of hydrated membranes was between 10 degrees C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…However, an increasing number of tropical seeds hitherto classed as orthodox are being included in a third behavioral class, which is characterized by sensitivity to different combinations of water content and chilling during storage. These seeds may be damaged when stored at 10-15°C, particularly during the transition from a liquid crystalline to a gel phase which occurs in their membranes upon subsequent rehydration (Sacandé et al 2001). Our results confirmed that storage in paper bags under normal ambient conditions permits preserving the viability of C. odorata seeds for at least 6 months, which may be of particular interest to ensure a local supply of seeds given the unpredictable climatology of the dry tropics.…”
Section: Discussionsupporting
confidence: 67%
“…However, an increasing number of tropical seeds hitherto classed as orthodox are being included in a third behavioral class, which is characterized by sensitivity to different combinations of water content and chilling during storage. These seeds may be damaged when stored at 10-15°C, particularly during the transition from a liquid crystalline to a gel phase which occurs in their membranes upon subsequent rehydration (Sacandé et al 2001). Our results confirmed that storage in paper bags under normal ambient conditions permits preserving the viability of C. odorata seeds for at least 6 months, which may be of particular interest to ensure a local supply of seeds given the unpredictable climatology of the dry tropics.…”
Section: Discussionsupporting
confidence: 67%
“…1, 2; Crane et al 2003). The loss of viability of intermediate seeds during dry storage has been attributed to phase transitions or amphiphile partitioning within the aqueous portion of the seed (Sacande´et al 1998(Sacande´et al , 2000(Sacande´et al , 2001 ONSET TEMPERATURE (°C) in C. carthagenensis seeds as a function of the water content of the seeds. The onset temperature of the transition is reported and represents the average value (points) and standard deviation (error bars) for seeds stored at 5°C for 10-120 days (see representative scans in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallization and melting of storage lipids are completely reversible in dry seeds, as is evident from the routine storage of many crop species (so-called orthodox seeds) at liquid nitrogen temperatures (< ¡135°C; Stanwood and Bass 1981; Walters et al 2004). We have used principles developed from the imbibitional chilling injury literature (Crowe et al 1989;Hoekstra et al 2001;Sacandé et al 2001;Golovina and Hoekstra 2003) and from the freeze-desiccation damage literature (Crowe and Crowe 1992;Steponkus et al 1995) to hypothesize about the mechanisms of damage induced when seeds with crystallized triacylglycerols are imbibed (Crane et al 2003(Crane et al , 2006. These hypotheses may be explained by decompartmentalization within cells because of altered hydrophilic and hydrophobic interactions on the liposome membrane.…”
Section: Introductionmentioning
confidence: 99%